(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
أشارت النتائج المخبرية على عينات ثمار الموز المجموعة من أسواق محافظتي اللاذقية وطرطوس خلال العامين (2011,2010) إلى وجود الأمراض الفطرية التالية في العينات المدروسة: الأنتراكنوز (Colletotrichum musae,Fusarium oxysporum (F4)), عفن التاج (Colletotrichum musae, F.oxysporum(F1) Ceratocystis paradoxa ,Thielaviopsis basicola, F.oxysporum (F2)), عفن الطرف الزهري (F.oxysporum (F3)), تبقع ثمار الموز(F.oxysporum (F4)), وعفن طرف السيجار(Verticillium theobromae ) وكان مرضى الأنتراكنوز وتعفن التاج أكثر الأمراض الفطرية انتشاراً في العينات المدروسة, وهذا هو التسجيل الأول لأمراض تعفن التاج, تبقع ثمار الموز, وتعفن الطرف الزهري في سورية. كان مستنبت PSA هو الأفضل لنمو وتبوغ فطر الفيوزاريوم بعزلاته المختلفة, بينما كان مستنبتPDA الأفضل للأجناس الأخرى. أظهرت الفطور المعزولة من الثمار قدرة عالية على إحداث الإصابة فقد لوحظت أول أعراض الإصابة بعد يومين من التحضين، وكانت أكثر وضوحاً عند العدوى بالجنسين Colletotrichum sp.وspp. Fusarium. The results showed that banana fruit samples, collected from Lattakian and Tartous markets during two 2010 and 2011 are carried of the following fungal diseases in the tested samples: Anthracnose (Colletotrichum musae,Fusarium oxysporum (F4)),Crown rot (Colletotrichum musae, F.oxysporum(F1) Ceratocystis paradoxa ,Thielaviopsis basicola, F.oxysporum (F2)), Blossom end rot (F.oxysporum (F3)), banana fruits spot (F.oxysporum (F4)), cigar end rot (Verticillium theobromae), Anthracnose and Crown rot fungal diseases, were more prevalent in the tested samples. This is the first record of Crown rot diseases, banana fruits spot,and Blossom end rot in Syria. The PSA medium was the most favorable for various Fusarium spp. growth and sporulation of fungi, while PDA medium was the suitable on banana fruits,where for other species. Isolated fungi showed a significant virulence, first symptoms of infection was observed after two days of infection and was more pronounced for Fusarium spp. and, Colletotrichum spp.